Penguatan Skill Editing Video Siswa Pondok Pesantren Al-Watoniyah Pusat Putri sebagai Upaya Pengembangan Diri di Era Digital (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aimed to equip students at Al-Watoniyah Central Girls’ Islamic Boarding School with video editing skills as an effort to address the rapid development of digital technology and promote digital competency improvement among young generations. The training activities were conducted through a combination of seminars, workshops, hands-on practices, and intensive mentoring provided by the community service team. The program was implemented on June 10, 2026, involving 15 participants consisting of students and teachers. Throughout the program, participants demonstrated high enthusiasm in participating in each training stage, including understanding basic video concepts, learning video editing software, and practicing the creation and editing of digital content. Active participation was also reflected through discussions, independent practices, and positive responses delivered by two participant representatives during the testimonial session. Evaluation results based on comparisons between pre-test and post-test scores indicated an improvement in participants’ knowledge and understanding of video editing techniques. This activity contributed positively to enhancing participants’ creativity, productivity, and readiness to utilize digital technology for learning purposes and skill development in the era of digital transformation.